2016
DOI: 10.1159/000452552
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Telbivudine and Entecavir Therapy on Nephritic Function and Drug Resistance in Patients with Hepatitis B Virus-Related Compensated Cirrhosis

Abstract: Background: To compare the impact of telbivudine (LDT) and entecavir (ETV) administration on nephritic function. Method: One hundred thirty patients diagnosed with hepatitis B virus (HBV)-related compensated cirrhosis were randomly divided into LDT (600 mg/d) or ETV (0.5 mg/d) groups. Results: The drug resistance rate was higher following LDT treatment compared to ETV treatment (16.9% vs. 1.5%, P=0.0006). The mean creatinine level decreased compared to baseline in the LDT group (0.81 vs. 0.94 mg/dl, P=0.000). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We found that: ETV resistant mutants can be effectively inhibited with monotherapy of a different NA as long as the NA, like TDF selected in this study for the rescue therapy, is as potent as ETV; resistant mutants can also be inhibited by addition of a weak NA like ADV while keeping ETV in the regimens; a combination of ETV with TDF does not seem to result in significantly superior efficacy compared to TDF monotherapy though it doubles the expense; and a double dose of ETV largely fails to overcome the ETV drug mutant resistance. A fundamental mechanism for the emergence of NA drug resistance is the introduction of mutated nucleotide in the HBV pol gene coding the RT domain, which leads to changes in both amino acids and conformations of RT that the small molecule inhibitors can no longer bind and inhibit efficiently [4,13,14]. It is appreciable that TDF can potently inhibit the ETV drug resistant mutants because the inhibition of wildtype HBV replication by TDF is equivalent to ETV if not stronger, and they differ in chemical structure and target different pockets in the RT domain [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that: ETV resistant mutants can be effectively inhibited with monotherapy of a different NA as long as the NA, like TDF selected in this study for the rescue therapy, is as potent as ETV; resistant mutants can also be inhibited by addition of a weak NA like ADV while keeping ETV in the regimens; a combination of ETV with TDF does not seem to result in significantly superior efficacy compared to TDF monotherapy though it doubles the expense; and a double dose of ETV largely fails to overcome the ETV drug mutant resistance. A fundamental mechanism for the emergence of NA drug resistance is the introduction of mutated nucleotide in the HBV pol gene coding the RT domain, which leads to changes in both amino acids and conformations of RT that the small molecule inhibitors can no longer bind and inhibit efficiently [4,13,14]. It is appreciable that TDF can potently inhibit the ETV drug resistant mutants because the inhibition of wildtype HBV replication by TDF is equivalent to ETV if not stronger, and they differ in chemical structure and target different pockets in the RT domain [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental mechanism for the emergence of NA drug resistance is the introduction of mutated nucleotide in the HBV pol gene coding the RT domain, which leads to changes in both amino acids and conformations of RT that the small molecule inhibitors can no longer bind and inhibit efficiently . It is appreciable that TDF can potently inhibit the ETV drug resistant mutants because the inhibition of wildtype HBV replication by TDF is equivalent to ETV if not stronger, and they differ in chemical structure and target different pockets in the RT domain .…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhosis was diagnosed based on histological assessments of the liver, clinical symptoms, endoscopic examination, laboratory analysis, and sonographic results. Diagnoses of compensated and decompensated cirrhosis were made following liver disease management guidelines, including Child-Turcotte-Pugh score (14). Child-Turcotte-Pugh scores of 5 or 6, 7-9, or 10-15 were treated as Child-Pugh class A, B, or C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The current therapy drugs include adefovir, tenofovir disoproxil fumarate, lamivudine (LAM), telbivudine and entecavir (11); however, LAM has been identified as having high drug resistance, and is no longer used as a first-line therapy for patients with CHB (12). Multiple clinical studies have proposed that entecavir may be used as a primary agent for patients with HBV-related liver cirrhosis irrespective of HBeAg serostatus (9,13,14). Entecavir is an antiviral agent that has been demonstrated to be an effective treatment of CHB (8).…”
Section: Introductionmentioning
confidence: 99%
“…CTP scores were mostly 5-6 and generally < 7, but as high as 9 in one study. Exclusion criteria were any decompensating events; HCV, HIV, or HDV infection; renal insufficiency; or excessive alcohol consumption [185][186][187][188][189][190][191].…”
Section: Inclusion/exclusion Criteria In Studies Of Compensated Cirrhmentioning
confidence: 99%